Rischi geologici e conservazione del patrimonio culturale in basilicata - Lazzari, Maurizio; Danesi, Maria; Lanza, Viviana (GEOmedia, 2010)
Geologic Risks and Cultural Heritage Conservation in the Risk Map of Historical-Architectonic Heritage in Basilicata GIS is an established tool for landslides census and cultural heritage cataloguing. The integration of these knowledge basis is possible using the GIS computational abilities. This study shows the results of a project realized by CNR-IBAM, AdB and Basilicata Region and carried out on a wide territory (30 municipalities) in order to define a Cultural Heritage Risk Map by a GIS structuring of Cultural Heritage and geological risk factors with tools design for the analysis of the Risk, spreading final data and result through a WebGis.